The contribution of mitochondria-associated endoplasmic reticulum membranes (MAMs) dysfunction in Alzheimer’s disease and the potential countermeasure - Li, Zehui; Cao, Yu; Pei, Hui; Ma, Lina; Yang, Yang; Li, Hao (Frontiers in Neuroscience, 2023)
Alzheimer’s disease (AD) is the most common neurodegenerative disease. There are many studies targeting extracellular deposits of amyloid β-peptide (Aβ) and intracellular neurofibrillary tangles (NFTs), however, there are no effective treatments to halt the progression. Mitochondria-associated endoplasmic reticulum membranes (MAMs) have long been found to be associated with various pathogenesis hypotheses of AD, such as Aβ deposition, mitochondrial dysfunction, and calcium homeostasis. However, there is a lack of literature summarizing recent advances in the mechanism and treatment studies. Accordingly, this article reviews the latest research involving the roles of MAM structure and tethering proteins in the pathogenesis of AD and summarizes potential strategies targeting MAMs to dissect treatment perspectives for AD.